Clinical efficacy of combination of pertuzumab, trastuzumab, and docetaxel for treatment of patients with HER2-positive breast cancer. Issue 38 (September 2019) - Liu, Yan-cui; Ma, Ying; An, Ning; Sun, Ping; Wang, Ying; Sun, Cheng
Abstract: Background: This study will systematically investigate the efficacy and safety of the combination of pertuzumab, trastuzumab, and docetaxel (PTD) for treatment of patients with HER2-positive breast cancer (HER2-PBC). Methods: A comprehensive literature search for this study will consist of 2 parts: electronic database records and gray literature. The electronic database literatures are searched from PubMed, EMBASE, Cochrane Library, Web of Science, Google Scholar, Allied and Complementary Medicine Database, Chinese Biomedical Literature Database, and China National Knowledge Infrastructure. All databases will be searched from inception up to the present. In addition, gray literatures, such as dissertations, ongoing trials, and so on, will also be searched. Two authors will independently read the records, extract data collection, and evaluate the risk of bias. RevMan V.5.3 software will be applied for statistical analysis. Results: This study will summarize up-to-date evidence of PTD for patients with HER2-PBC via overall survival, complete response, cancer-specific survival, recurrence-free survival, disease-free survival, quality of life, and toxicities. Conclusion: This study will provide efficacy and safety of PTD for HER2-PBC.